ANALISA PENYEBAB ADANYA BERKAS REKAM MEDIS SEMENTARA DI RSI SITI RAHMAH - Dewi Mardiawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Temporary medical records occur because medical record files that are not found on the storage rack are caused by misplaced medical records and borrowed by the room clerk to complete the resume. The repatriation of the medical record file was more than the time determined so that it had an impact on the patients who were treated again at the Siti Rahmah Hospital in Padang. So, to speed up the service of medical records officers make temporary medical record files. The results of this study found that the availability of human resources is good enough and know the meaning and function of the temporary medical record, but the responsibilities and attitudes of officers are not good, because there are still medical record files that have not been found or the doctor has not returned the medical record file to the room storage. This research was conducted at the Islamic Hospital of Siti Rahmah Padang on 20 to 28 August 2018. The informants in this study were 6 medical records officers namely the head of medical records, registration medical records officers, and 4 storage medical records officers. Data collection techniques in this study are in-depth interviews with informants and observations of officers. Analysis of the data used in this study is Colaizzi's theory. Data validation used is the extension of observation, this type of research is qualitative with a phenomenological approach. The conclusion of the study was that the medical records officer at the Siti Rahmah Islamic Hospital was sufficient, but the responsibilities of the officers were still lacking. Suggestions in this study are the addition of expedition books for temporary files so that the temporary files do not disappear because only one sheet.